The Analysis of the Criticality of Data Integrity in Human Resources Information Systems - Dickson Mdhlalose (Advanced Research in Economics and Business Strategy Journal, 2025)
Introduction: In the fields of information technology and data management, data integrity is a fundamental concept. Data integrity ensures the accuracy, consistency, and dependability of data throughout its existence. This study aims to establish best practices for preserving accurate and trustworthy HR data and to assess the importance of information integrity in HRIS, examining its impact on business decisions, compliance with regulations, and employee confidence. Method: Data from secondary sources were used in this investigation. To assist the study, relevant textbooks were reviewed, and secondary material was gathered online, utilising various search engines. Results: Due to the diverse sources and processes from which HR inputs come, data integrity in HRIS is seldom attained. Organisations can save time, money, and resources by establishing and maintaining data integrity, thereby preventing critical decisions from being made based on incomplete or erroneous data. A fundamental gap with major organisational consequences is the lack of research on data integrity in human resource information systems. The usefulness of this study lies in its thorough presentation of data integrity challenges in the human resources information system. This analysis was limited to secondary data and the limited scholarly literature. Conclusion: For HRIS to manage employee data accurately, consistently, and securely, data integrity is essential. It is essential for upholding compliance, facilitating informed decision-making, and fostering trust within businesses. HRIS runs the danger of operational failures, legal issues, and reputational harm in the absence of strong data integrity controls. Data integrity must therefore be given top priority if HR operations are to continue succeeding and the organisation is to expand.